VLADIMIR STOJŠIN – THE GENESIS OF A CROSSOVER (Филолошки студии, 2021)
The paper deals with the status of the children’s novels The Cinema in a Matchbox and The Champion Through the Window by Vladimir Stojšin (1935–1994) in relation to their affiliation with literature for all ages, i.e. crossover literature. Today, Stojšin is best known as a writer for children, although at the time when he published his first novel for young people, he had already published praised prose works of a very modern orientation. From the very beginning, his novels for children have been received as literature for all ages. As a writer for children, Stojšin remained largely attached to themes and motifs belonging to the narrative worlds of his previous works. Focusing on the example of the transformation of a character of a prostitute from a novel for adults into the character of platonic love interest of the hero-narrator from the novels for children, the text identifies the narrative devices by which this transformation was carried out. The conceptual apparatus of classical and postclassical narratology was used in the analysis.